Topographic Description of Metacarpal Tendons and Ligaments of Anatoly Donkey by Ultrasonography and Introducing a New Ligament - Mohammad Naser Nazem; Sayed Mohsen Sajjadian; Dariush Vosough; Ali Mirzaesmaeili (Negah Institute for Scientific Communication, 2015)
Introduction: Topographic anatomy of the tendons and ligaments in healthy cases provides a normal atlas to diagnose abnormalities. The aim of this study was to provide ultrasonography description of the palmar tendons and ligaments of the Anatoly donkey. Methods: The metacarpal regions of 6 healthy Anatoly donkeys were prepared for ultrasonography and divided to 6 levels (1a, 1b, 2a, 2b, 3a, 3b), each 3 cm long apart. For better description, 2 left and right forelimbs were anatomically studied too. Results: All the structures started to appear with an acceptable contrast and visibility at 1b level. Echogenicity of deep digital flexor tendons (DDFT) from 2b level was hyperechoic to isoechoic compared to superficial digital flexor tendons (SDFT) and suspensory ligament (SL) from this level observed the branching area was hyperechoic in comparison to DDFT and SDFT; however MSL and LSL were hypoechoic compared to SDFT and DDFT. Also the inferior check ligament (ICL) and new discovered ligament (second superior check ligament) had been detected in both anatomical and ultrasonographic studies. There were not any echogenicity differences between right and left forelimbs. Conclusion: Previous investigations have proved that there is no difference between the echogenicity of each ligament and tendon at different levels in the left and right limbs which was confirmed in the current study as well. The findings of our study are also highly compatible with the previous findings in horses regarding echogenicity and shape of the palmar tendons and ligaments. Generally it is assumed that transverse images provide a better image of tendons and ligaments.